Infectious Media: Cholera and the Circulation of Texts in the Finnish Press, 1860–1920. Issue 1 (2nd January 2023) - Paasikivi, Sofia; Salmi, Hannu; Vesanto, Aleksi; Ginter, Filip
Abstract : Cholera was the emblematic disease of the nineteenth-century Europe. This article explores the cultural ramifications of cholera by concentrating on the ways in which public discourse participated in circulating information on the disease. It focuses on the reuse of texts about cholera in the Finnish press from 1860 to 1920. The most difficult cholera epidemics in Finland were the first ones in the 1830s and 1850s, and the number of casualties dropped significantly towards the end of the century. At the same time, however, cholera was discussed more than ever, and there was the rising curve of the references to cholera from the 1860s onwards. In Finland, the public discourse on cholera was also entangled with the rising nationalism towards the end of the nineteenth century.